Perlindungan Pencipta Lagu atas Pelanggaran Hak Maternitas dan Hak Intergritas Berdasarkan Undang-Undang Nomor 28 Tahun 2014 - Ramanda Josian Kusnadi; Tatty Aryani Ramli (UNISBA Press, 2022)
Abstract..Intellectual Property Rights are rights that arise for the results of thought processes that produce a product or process that is useful for humans. In essence, IPR is the right to enjoy economically the results of intellectual creativity. Objects regulated in IPR are works that arise or are born because of human intellectual abilities. Basically there are two important concepts in copyright law, namely moral rights and economic rights. These two concepts are values ​​that are highly valued in copyright law. Why is it called